2022
DOI: 10.1136/bmjpo-2021-001275
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with the risk of HIV infection among HIV-exposed infants in Malawi: 2013–2020

Abstract: BackgroundDespite the availability of individual-level data of infants accessing HIV DNA-PCR testing service, there has been little in-depth analysis of such data. Therefore, we describe trends in risk of HIV infection among Malawi’s HIV-exposed infants (HEI) with DNA-PCR HIV test result from 2013 to 2020.MethodsThis is an implementation study using routinely collected patient-level HIV DNA-PCR test result data extracted from the national Laboratory Management Information System database managed by the Departm… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…The studies published between January 2012 and March 2022 were carried out in a range of East African countries; namely, Burundi [ 57 ], Comoros [ 57 ], Ethiopia [ 25 , 45 , 57 74 ], Kenya [ 57 , 75 78 ], Malawi [ 25 , 45 , 57 74 , 79 ], Mozambique [ 57 , 76 78 , 80 ], Rwanda [ 57 ], South Sudan [ 81 ], Tanzania [ 82 , 83 ], Uganda [ 39 , 57 , 84 87 ], Zambia [ 57 , 88 90 ], and Zimbabwe [ 57 , 91 96 ]. Studies conducted among eligible pregnant/postpartum women, infants and service providers were included in the analysis.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The studies published between January 2012 and March 2022 were carried out in a range of East African countries; namely, Burundi [ 57 ], Comoros [ 57 ], Ethiopia [ 25 , 45 , 57 74 ], Kenya [ 57 , 75 78 ], Malawi [ 25 , 45 , 57 74 , 79 ], Mozambique [ 57 , 76 78 , 80 ], Rwanda [ 57 ], South Sudan [ 81 ], Tanzania [ 82 , 83 ], Uganda [ 39 , 57 , 84 87 ], Zambia [ 57 , 88 90 ], and Zimbabwe [ 57 , 91 96 ]. Studies conducted among eligible pregnant/postpartum women, infants and service providers were included in the analysis.…”
Section: Resultsmentioning
confidence: 99%
“…The studies published between January 2012 and March 2022 were carried out in a range of East African countries; namely, Burundi [57], Comoros [57], Ethiopia [25,45,[57][58][59][60][61][62][63][64][65][66][67][68][69][70][71][72][73][74], Kenya [57,[75][76][77][78], Malawi [25,45,[57][58][59][60][61][62][63][64][65][66][67][68][69][70][71][72][73][74]79], Mozambique [57,[76][77]…”
Section: Characteristics Of Included Studies On Prevention Of Mother-...mentioning
confidence: 99%
See 1 more Smart Citation
“…While the children over 18 months of age contributed to only 20% of the study population, this study suggests that this age group of severely malnourished children need to be studied further. A large longitudinal study in Malawi among HIV exposed children showed that HIV prevalence increased by age of the HIV exposed child [ 32 ]. A similar study in rural Kenya showed that child age over 6 months at enrolment was associated with HIV infection [ 16 ].…”
Section: Resultsmentioning
confidence: 99%